Depressive symptomatology is associated with problematic smartphone use severity in adolescents: The mediating role of cognitive emotion regulation strategies - Arrivillaga, Christiane; Elhai, Jon; Rey-Peña, Lourdes; Extremera-Pacheco, Natalio (MUNI, 2023)
Problematic smartphone use (PSU) has been widely studied, and recent research has examined the affective and cognitive process risk factors that underlie its development and maintenance. Based on the Interaction of Person–Affect–Cognition–Execution model for problematic internet use, the present study analyzed the mediating role of cognitive emotion regulation strategies in the link between depressive symptomatology and PSU severity in adolescents. The sample consisted of 2,197 adolescents aged 12 to 19 years from southern Spain, who completed self-report questionnaires of depressive symptoms (Depression Anxiety Stress Scale–21), cognitive emotion regulation strategies (Cognitive Emotion Regulation Strategies Questionnaire), and PSU severity (Smartphone Addiction Scale–Short Version). We used the SPSS PROCESS macro to conduct parallel mediation analyses. The results demonstrated significant indirect/mediation effects from depressive symptoms to PSU severity through cognitive emotion regulation strategies, including other-blame, catastrophizing, rumination (i.e., maladaptive), and refocus on planning (i.e., adaptive). The implications of this study include that specific teaching about these strategies may help reduce PSU severity in adolescents.
Keywords: Adolescentes - Psicología; Tecnología - Aspectos sociológicos; Teléfonos móviles y jóvenes; Depresión mental; Emociones; Adolescentes; Psicología; Tecnología; Aspectos sociológicos